Distribution of mRNA for vanilloid receptor subtype 1 (VR1), and VR1-like immunoreactivity, in the central nervous system of the rat and human - Mezey, Éva (The National Academy of Sciences, 2000)
The cloned vanilloid receptor VR1 has attracted recent attention as a molecular integrator of painful stimuli on primary sensory neurons. The existence of vanilloid-sensitive neurons in the brain is, however, controversial. In this study, we have used an antibody and a complementary RNA probe to explore the distribution of neurons that express VR1 in rat and in certain areas of human brain. In the rat, we observed VR1-expressing neurons throughout the whole neuroaxis, including all cortical areas (in layers 3 and 5), several members of the limbic system (e.g., hippocampus, central amygdala, and both medial and lateral habenula), striatum, hypothalamus, centromedian and paraventricular thalamic nuclei, substantia nigra, reticular formation, locus coeruleus, cerebellum, and inferior olive. VR1-immunopositive cells also were found in the third and fifth layers of human parietal cortex. Reverse transcription–PCR performed with rat VR1-specific primers verified the expression of VR1 mRNA in cortex, hippocampus, and hypothalamus. In the central nervous system, neonatal capsaicin treatment depleted VR1 mRNA from the spinal nucleus of the trigeminal nerve, but not from other areas such as the inferior olive. The finding that VR1 is expressed not only in primary sensory neurons but also in several brain nuclei is of great importance in that it places VRs in a much broader perspective than pain perception. VRs in the brain (and putative endogenous vanilloids) may be involved in the control of emotions, learning, and satiety, just to name a few exciting possibilities.